TNFα-Signaling Modulates the Kinase Activity of Human Effector Treg and Regulates IL-17A Expression - Urbano, Paulo C. M.; He, Xuehui; Heeswijk, Bennie van; Filho, Omar P. S.; Tijssen, Henk; Smeets, Ruben L.; Joosten, Irma; Koenen, Hans J. P. M. (Frontiers in Immunology, 2020)
Maintenance of regulatory T cells CD4+CD25highFOXP3+ (Treg) stability is vital for proper Treg function and controlling the immune equilibrium. Treg cells are heterogeneous and can reveal plasticity, exemplified by their potential to express IL-17A. TNF-TNFR2 signaling controls IL-17A expression in conventional T cells via the anti-inflammatory ubiquitin-editing and kinase activity regulating enzyme TNFAIP3/A20 (tumor necrosis factor-alpha-induced protein 3). To obtain a molecular understanding of TNF-signaling on IL-17 expression in human effector (effTreg, CD25highCD45RA-) Treg subset, we here studied the kinome activity regulation by TNF-signaling. Using FACS-sorted naïve (naïveTreg, CD25highCD45RA+) and effector Treg subsets, we demonstrated a reciprocal relationship between TNFα and IL-17A expression; effTreg (TNFαlow/IL-17Ahigh) and naïveTreg (TNFαhigh/IL-17Alow). In effTreg TNFα-TNF receptor-2 signaling prevented IL-17A expression, whereas inhibition of TNFα signaling by clinically applied anti-TNF antibodies led to increased IL-17A expression. Inhibition of TNFα signaling led to reduced TNFAIP3 expression, which by using siRNA inhibition of TNFAIP3, appeared causally linked to increased IL-17A expression in effTreg. Kinome activity screening of CD3/CD28 activated effTreg revealed that anti-TNF mediated neutralization led to increased kinase activity. STRING association analysis revealed that the TNF suppression effTreg kinase activity network was strongly associated with kinases involved in TCR, JAK, MAPK and PKC pathway signaling. Small molecule-based inhibition of TCR and JAK pathways prevented the IL-17 expression in effTreg. Together, these findings stress the importance of TNF/TNFR2 in regulating the kinase architecture of antigen-activated effTreg and controlling IL-17 expression of the human Treg. These findings might be relevant for optimizing anti-TNF based therapy and may aid in preventing Treg plasticity in case of Treg-based cell therapy.